115k views
1 vote
Solve the equation y=ax-b for the varible x

Solve the equation y=ax-b for the varible x-example-1

2 Answers

7 votes

Final answer:

To solve the equation y=ax-b for the variable x, add b to both sides and divide both sides by a.

Step-by-step explanation:

To solve the equation y=ax-b for the variable x, we can start by isolating the variable. In this equation, we have y=ax-b. To get rid of the -b term, we can add b to both sides of the equation: y+b=ax. Next, we can divide both sides by a to solve for x: (y+b)/a=x. To solve the equation y = ax - b for the variable x, we want to isolate x on one side of the equation. Here are the steps to do this:

Add b to both sides of the equation to get y + b = ax.

Divide both sides of the equation by a to get (y + b) / a = x.

So the solution for x in terms of y is x = (y + b) / a.

An example of this is the linear equation y = 9 + 3x. Here, the constant term is 9 and the slope is 3. This can be rearranged to x = (y - 9) / 3 by following the above steps.

Remember, slope and y-intercept are important components of a linear equation. In the form y = a + bx, b represents the slope, and a represents the y-intercept. To find x in terms of y, the process involves undoing what has been done to x, by reversing the operations applied to it in the equation.

User Musa Usman
by
5.9k points
10 votes

Answer:

Step-by-step explanation:

Answer is b

User Milan Neninger
by
5.1k points